2014
DOI: 10.1007/s10518-014-9593-1
|View full text |Cite
|
Sign up to set email alerts
|

Models for reproducing the damage scenario of the Lorca earthquake

Abstract: A damage scenario modelling is developed and compared with the damage distribution observed after the 2011 Lorca earthquake. The strong ground motion models considered include five modern ground motion prediction equations (GMPEs) amply used worldwide. Capacity and fragility curves from the Risk-UE project are utilized to model building vulnerability and expected damage. Damage estimates resulting from different combinations of GMPE and capacity/fragility curves are compared with the actual damage scenario, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
(22 reference statements)
2
6
0
3
Order By: Relevance
“…In the recent years a number of catastrophic earthquakes occurring in Europe resulted in significant damage to cultural heritage buildings. The damage observed in different types of structures after Lorca earthquake (Spain) in 11th May 2011 was discussed in several publications such as [1][2][3][4][5][6][7][8]. Brandonisio et al and Lagomarsino [9][10] showed the effects of L'Aquila earthquake (Italy) occurred in 9th April 2009.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years a number of catastrophic earthquakes occurring in Europe resulted in significant damage to cultural heritage buildings. The damage observed in different types of structures after Lorca earthquake (Spain) in 11th May 2011 was discussed in several publications such as [1][2][3][4][5][6][7][8]. Brandonisio et al and Lagomarsino [9][10] showed the effects of L'Aquila earthquake (Italy) occurred in 9th April 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Control spectra or specific response spectra are also used to estimate the seismic hazard and risk in cities or specific sites (Rivas-Medina et al, 2011, 2014a.…”
Section: Introductionmentioning
confidence: 99%
“…(b) Abrahamson & Silva (2008). (c) Campbell & Bozorgnia (2008), citados en el apartado 2.1.1.2 (Rivas-Medina et al, 2014) ………….…………………………………………………………………………………………………………..…”
Section: Figura 254unclassified
“…Otros trabajos analizan el comportamiento sísmico de los edificios monumentales de esta ciudad según la variante de RISK-UE para este tipo de edificaciones (Irizarry, 2004; Pág Lantada et al, 2010), así como el de edificaciones de carácter especial como escuelas y hospitales (Safina, 2003;García-García, 2010;Valcárcel, 2013). Cardona et al (2012) En lo relativo a la Región de Murcia, además de los proyectos RISMUR (Benito et al, 2006;Benito et al, 2015) y SISMIMUR (2006, destacan los recientes estudios realizados en la ciudad de Lorca a raíz del terremoto de 2011 (Feriche et al, 2012a;Martínez-Cuevas;CARM;Rivas-Medina et al, 2014, Salgado-Gálvez et al, 2015Martínez-Cuevas & Gaspar-Escribano, 2016…”
Section: Estudios Sobre Riesgo Sísmico En áReas Urbanas En La Penínsuunclassified
See 1 more Smart Citation